Effect of Salinity Stress on Plant Green Weight and Nutrient Value of Soybean (Glycine max (L.) Merrill) Cultivars - Tuncturk, Murat; Yasar, Fikret; Tuncturk, Ruveyde (Asian Journal of Chemistry, 2010)
Soil salinity is a major limitation to crop production in many areas of the world. A pot experiment was carried out with soybean cultivars to investigate the effects of salinity stress on plants growth and nutrient composition at 150 mM NaCl concentration under greenhouse conditions. Twelve soybean cultivars were exposed to salinity treatments (0 and 150 mM NaCl and control). All cultivars were harvested 45 d after plantation. Green parts of 45-day old plant weights were recorded. Soybean cultivar plants were divided into root, shoot and leaf parts for nutrient (K+, Na+, Ca2+ and Cl–) content measurements. Salinity stress negatively affected soybean cultivars and the effects varied according to the salt tolerance of the cultivars. Generally, salinity reduced the green weight. Salt stress decreased K+, Ca2+, contents and K+/Na+ rations in plants, but significantly increased Na+ and Cl– content in the roots, shoots and leaves of all cultivars. In the salt treatment, K+, Ca2+, concentration and K+/Na+ rations were high in leaf compared with those in roots and shoots. Howover, the highest increase in Na+ and Cl– contents were observed in the roots and shoot of plants. Under salinity, Mancon, Stresland and Althow varieties retained the highest K+ and Ca2+ content in leaves, related to K+ the varieties were not effected under 150 Mm NaCl treatment.